The Impact Of Profitability, Company Size, Green Accounting, Media Disclosure, And The Board Of Commissioners On Csr Disclosure - Kevin Kenesis; Stefanus Dimas Ryan Saputro (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
The research aimed to investigate the influence of alterations in green accounting, firm size, board commissioner count, media disclosure, and profitability on CSR disclosure. Corporate Social Responsibility (CSR) has emerged as a critical factor, second only to financial performance, for publicly traded companies, hence necessitating the evaluation of additional variables in research. This study replicates the research conducted by Katarina Agnes (2023), with the addition of four control variables and modifications to the hypothesis testing program. The primary distinctions encompass the incorporation of four control variables, the transition from SPSS to STATA version 16 for hypothesis testing, and the research sample comprising 280 data points from 70 manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The study process encompasses descriptive statistical analyses, classical assumption evaluations, model specification assessments, and hypothesis testing. The findings demonstrate that green accounting, firm size, and media exposure significantly influence CSR disclosure, while the number of board commissioners and profitability do not significantly affect CSR disclosure.